Joint phase error estimation and sparse scene restoration algorithms for frequency agile radar - Zhiting Fei; Jindong Zhang; Xiaohua Zhu; Xun Ding (IET Radar, Sonar & Navigation, 2021)
Abstract Frequency agile radar (FAR) systems have been demonstrated to have outstanding performance in electronic counter‐countermeasures (ECCM). With increased bandwidth in which FAR can switch carrier frequency, the phase errorswill appear at the corresponding frequency point, resulting in the decrease of coherence of the system. To accomplish phase error correction and range and velocity information extraction of the target simultaneously, a joint phase error estimation and sparse scene restoration algorithm based on sparse recovery (JPSA‐SR) is proposed here. To further reduce the computational complexity of the algorithm, a joint phase error estimation and sparse scene restoration algorithm based on alternating direction method of multipliers (JPSA‐ADMM) is also proposed. Numerical examples show the effectiveness of the proposed algorithms.